2010
DOI: 10.1117/6.0000005
|View full text |Cite
|
Sign up to set email alerts
|

Video browsing interfaces and applications: a review

Abstract: Abstract. We present a comprehensive review of the state of the art in video browsing and retrieval systems, with special emphasis on interfaces and applications. There has been a significant increase in activity (e.g., storage, retrieval, and sharing) employing video data in the past decade, both for personal and professional use. The ever-growing amount of video content available for human consumption and the inherent characteristics of video data-which, if presented in its raw format, is rather unwieldy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 81 publications
0
48
0
Order By: Relevance
“…A typical video browsing tool -although a very simple one -is a common video player that provides navigation facilities for changing the playback position in a video (e.g., with a seeker-bar). Many browsing tools, with better interaction means than provided by a typical video player, have been presented in the literature (for a detailed review see [29]). While many of them are advanced navigation methods (e.g., [7,8]), extended video players (e.g., [10,14,18]) or enhanced video content visualizations [6], some are highly sophisticated browsing tools (e.g., [1,25,30]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical video browsing tool -although a very simple one -is a common video player that provides navigation facilities for changing the playback position in a video (e.g., with a seeker-bar). Many browsing tools, with better interaction means than provided by a typical video player, have been presented in the literature (for a detailed review see [29]). While many of them are advanced navigation methods (e.g., [7,8]), extended video players (e.g., [10,14,18]) or enhanced video content visualizations [6], some are highly sophisticated browsing tools (e.g., [1,25,30]).…”
Section: Introductionmentioning
confidence: 99%
“…Although many tools have been proposed for interactive video search (see [29]), it is not obvious how well these tools perform for specific search tasks and for specific user groups such as expert and novice users [32,37]. It is also non-trivial to directly compare the tools without a common user study.…”
Section: Introductionmentioning
confidence: 99%
“…The user can browse through the abstract representations to locate the desired videos. A detailed review on video browsing interfaces, and applications can be found in (Schoeffmann et al, 2010). There are two basic strategies to show the retrieval results.…”
Section: Shot Boundaries Are Fundamental Units Of Videosmentioning
confidence: 99%
“…The video browsing and associated problem has been investigated by the research community for decades, [72]. However, the growing use of 3D video and the specific characteristics of this type of visual information make 3D video browsing a more interesting and challenging problem.…”
Section: Video Browsingmentioning
confidence: 99%
“…For example, once an interesting topic has been identified through display of the key-frames, a simple operation as a click on the respective key-frame can initiate video playback of the original content at that particular instant. Many video browsing methods have been proposed for 2D video [72]. However, to the best of the authors' knowledge, in the case of 3D video there are no works reported in the literature.…”
Section: Video Browsingmentioning
confidence: 99%